(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Effective collaboration between social workers and nurses is crucial for delivering comprehensive care and promoting positive health outcomes for patients. This paper explores the collaborative strategies, challenges, and opportunities inherent in the partnership between these two professions within healthcare settings. By leveraging their unique expertise and perspectives, social workers and nurses can address the complex needs of individuals, including social determinants of health, psychosocial support, and care coordination. Despite challenges such as role clarification, communication barriers, and resource limitations, opportunities for growth and innovation abound through interdisciplinary training, technology integration, quality improvement initiatives, advocacy efforts, and research endeavors. Ultimately, by working together synergistically, social workers and nurses can empower patients, promote health equity, and advance the delivery of patient-centered care.